Estimating Premorbid Intelligence among Older Adults: The Utility of the AMNART - Deborah A. Lowe; Steven A. Rogers (Journal of Aging Research)
This study examines the utility of the American version of the National Adult Reading Test (AMNART) as a measure of premorbid intelligence for older adults. In a sample of 130 older adults, aged 56 to 104, the AMNART was compared to other tests of premorbid intelligence. The results revealed that AMNART-estimated IQ was significantly higher than other premorbid estimates. Across specific educational groups (i.e., 0–12, 13–16, and 17 or more years of education), AMNART-estimated IQ was inflated relative to all other premorbid estimates. The AMNART also declined as cognitive impairment increased, and there was a significant interaction between aging-related diagnostic group and premorbid estimate. The AMNART may therefore overestimate premorbid ability relative to other premorbid measures, particularly among those with greater cognitive impairment and lower levels of education. These results suggest that the AMNART should be used cautiously among older adults and in conjunction with other estimates of premorbid ability.